(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Chitosan has been produced from shrimp waste by chemical method involving demineralization, deproteinization and deacetylation. The quality of chitosan depends on the conditions of the chemical extraction process. The results showed that 3% HCI and 4% NaOH were suitable concentration for demineralization and deproteinization, respectively at ambient temperature (28±2oC). Chitosan with a high degree of deacetylation (81.24%) and high solubility (97.65%) was obtained by deacetylation with 60% NaOH for 24 hours at 60°C. Purified chitosan was characterized for intrinsic viscosity (13.2dl/g), molecular weight (1.05×106 Dalton), FBC (427.98%), WBC (537.29%) as well as yield (15.4%). DOI: http://dx.doi.org/10.3329/jbau.v12i1.21405 J. Bangladesh Agril. Univ. 12(1): 153-160, June 2014